ARGUMENTASI FILSAFAT-TEOLOGIS TERHADAP MAKNA ELEMEN ROTI DAN ANGGUR PERJAMUAN KUDUS DALAM SEJARAH GEREJA - Sostenis Nggebu (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
The problem of this article discusses the meaning of the elements of the Holy Communion that have developed in church history. There are diverse views on the elements of the Lord's Supper that influence the doctrine of the Lord's Supper. The purpose of this discussion is to explain the philosophical and religious views of the Eastern world surrounding the concept of the elements of the Holy Communion. The method used is literature study. As a result, the meaning of the elements of the Lord's Supper has been influenced by Eastern philosophies and religious views in the early church period, so it is often seen as a change in substance (transubstantiation). The church serves holy communion to reflect faith in remembering Christ's sacrificial work on the cross for the forgiveness of sinners. Believers should be awakened to remember the great work of Christ who was willing to sacrifice for the sake of His people. So every time the congregation receives Holy Communion it should be greeted with faith and receive the service of bread and wine as a symbol of God's presence in the midst of His people. In conclusion, the Holy Communion element is only a sign of faith to remember Christ's work for the salvation of His people, and not as the real body and blood of Christ.